Removal of Manganese and Copper from Aqueous Solution by Yeast Papiliotrema huenov - Nguyen Van, Phu; Thi Hong Truong, Hai; Pham, Tuan Anh; Le Cong, Tuan; Le, Tien; Thi Nguyen, Kim Cuc (Mycobiology, 2021)
Papiliotrema huenov was previously reported to be highly tolerant of a range of extremely toxic heavy metals. This study aimed to identify the potential of P. huenov to remove manganese and copper from aqueous solution. Physical conditions which affect removal of Mn(II) and Cu(II) were determined. Optimal temperature for adsorption of both metal ions was 30 °C, and optimal pH for maximum uptake of Mn(II) and Cu(II) were 5 and 6, respectively. Under these conditions, living cells of P. huenov accumulated up to 75.58% of 110 mg/L Mn(II) and 70.5% of 128 mg/L Cu(II) over 120 h, whereas, the removal efficiency of metal ions by dead cells over 1 h was 60.3% and 56.5%, respectively. These results indicate that living cells are more effective than dead biomass for bioremediation, but that greater time is required. The experimental data extends the potential use of P. huenov in biosorption and bioaccumulation of toxic heavy metals to copper and manganese, two of the most common industrial contaminants.
Keywords: copper; Papiliotrema huenov; biosorption; bioaccumulation; manganese